Advance Care Planning and Patient Preferences in a Feasibility Pilot Study to Improve End‐of‐Life Communication among Men with Metastatic Urological Malignancies. Issue 6 (November 2018) - Pannell, Stephanie C.; Laviana, Aaron A.; Huen, Kathy H.Y.; Shelton, Jeremy B.; Kwan, Lorna; Bennett, Carol J.; Lorenz, Karl A.; Bergman, Jonathan
Abstract : Introduction: : Rates of advance care planning for patients with cancer are poor despite efforts to enhance discussions regarding goals of care. Good patient‐physician communication is critical to providing quality end‐of‐life care and, thus, it is important to identify effective interventions to improve systems through which patient preferences are addressed. Methods: : To improve rates of advance care planning as well as examine patient preferences regarding end‐of‐life care, we developed an integrated urology‐palliative care clinic. All patients with a new diagnosis of a metastatic urological malignancy or castration resistant prostate cancer seen in a urology clinic within the Veterans Affairs Greater Los Angeles Healthcare System were offered a palliative care referral to be performed immediately after their urology appointment. The primary outcome was completion of an advance directive or POLST (Physician Orders for Life‐Sustaining Treatment) form and the secondary outcome was patient preference regarding end‐of‐life care. Results: : A total of 59 patients were enrolled in the study between February 2012 and October 2016, and no patients were lost or excluded. There were 25 eligible patients who declined enrollment. Overall 85% of patients completed an advance directive or POLST form, and 98% chose to withhold cardiopulmonary resuscitation, advanced cardiac life support and artificially administered nutrition. Conclusions: : High levels of advance care planning are achievable in an integrated urology‐palliative care clinic and the majority of patients with a terminal illness are averse to aggressive end‐of‐life care.